Prominent Role of Utilities in the Electric Vehicle - S.Manoj, Dr. R.Krishnakumar (International Journal of Control and Automation, 2020)
Electric Vehicles (EVs) provides the possible reduction in the emission of Greenhouse gas for the electric vehicle consumers. Accordingly, awareness among the consumers to use the Electric Vehicles are required. At the same time, the Electric Vehicles face the challenge in terms of the Charging time and Range. In prior to that we propose the utilities of electric vehicle which in turn benefits the customers in many ways comparing to the Fuel injected Vehicle. A host of studies demonstrate benefits to society and to all electricity consumers from increased EV adoption. Also it is obvious that the utilities can shore up increased adoption and beneficial integration of EVs into the electric system to benefit their customers. Utilities are a trusted source of information about charging arrangement decisions, have built up associations with their clients, and can convey and instruct on the advantages of EVs.